2017
DOI: 10.1002/bmb.21105
|View full text |Cite
|
Sign up to set email alerts
|

Update on research and application of problem‐based learning in medical science education

Abstract: Problem-based learning (PBL) is a unique form of pedagogy dedicated to developing students' self-learning and clinical practice skills. After several decades of development, although applications vary, PBL has been recognized all over the world and implemented by many medical schools. This review summarizes and updates the application and study of PBL in medical education through the literature published between 1993 and early 2017. It focuses on understanding real medical PBL courses and ways to improve PBL t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 102 publications
0
34
0
1
Order By: Relevance
“…Furthermore, they believed that TBL could improve their abilities to communicate with each other and solve difficulties. Previous studies have demonstrated that CBL, PBL and TBL can obtain excellent outcomes in various courses [27][28][29]. In this study, we integrated CBL, PBL and TBL with the flipped classroom to form an organic integrity: the FC-integration model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they believed that TBL could improve their abilities to communicate with each other and solve difficulties. Previous studies have demonstrated that CBL, PBL and TBL can obtain excellent outcomes in various courses [27][28][29]. In this study, we integrated CBL, PBL and TBL with the flipped classroom to form an organic integrity: the FC-integration model.…”
Section: Discussionmentioning
confidence: 99%
“…This fills a knowledge gap by not only examining the potential benefits of ICE on CR within physical therapy education, which is limited, but also by documenting the additional benefits of concurrent PBL, with detailed information about the implementation thereof. The positive attributes of PBL coursework were reinforced by Fan et al [7], who noted enhanced reflective practice and CR. Moreover, the utilization of PBL within curricula is of growing prominence as national physical therapy licensure examinations have steadily increased the number of case-based clinical questions to determine entry-level readiness [10].…”
mentioning
confidence: 99%
“…Regrettably, assessments of CR during ICE within physical therapy education are sparse; the majority of investigations have been performed in other allied health fields [3,5,6]. Similarly, problem-based learning (PBL), a classroom model that creates a learner-centered environment where students solve complex clinical situations in a small-group format, has garnered significant attention [7]. Although assessments of the impact of PBL have varied, improved examination scores, social and cognitive domain performance, and self-reported CR have been noted, primarily in studies in the medicine, pharmacy, dental, nursing, and occupational therapy literature [7].…”
mentioning
confidence: 99%
See 2 more Smart Citations